2021
DOI: 10.1186/s12933-021-01384-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of admission hyperglycemia on short and long-term prognosis in acute myocardial infarction: MINOCA versus MIOCA

Abstract: Background The prognostic role of hyperglycemia in patients with myocardial infarction and obstructive coronary arteries (MIOCA) is acknowledged, while data on non-obstructive coronary arteries (MINOCA) are still lacking. Recently, we demonstrated that admission stress-hyperglycemia (aHGL) was associated with a larger infarct size and inflammatory response in MIOCA, while no differences were observed in MINOCA. We aim to investigate the impact of aHGL on short and long-term outcomes in MIOCA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 41 publications
2
47
0
Order By: Relevance
“…Several studies have reported that stress hyperglycemia is independently related to increased mortality and larger infarct size in patients with MI [ 3 , 18 , 19 ]. Paolisso et al reported that admission hyperglycemia is also an effective predictor of short and long-term prognosis in patients with AMI, including those with MINOCA, indicating that hyperglycemia may play a direct role in microvascular dysfunction [ 5 ]. While these data suggest that ABG can be considered a predictor of AMI prognosis, the predictive effectiveness of ABG depends on its definition and the threshold used to characterize stress hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that stress hyperglycemia is independently related to increased mortality and larger infarct size in patients with MI [ 3 , 18 , 19 ]. Paolisso et al reported that admission hyperglycemia is also an effective predictor of short and long-term prognosis in patients with AMI, including those with MINOCA, indicating that hyperglycemia may play a direct role in microvascular dysfunction [ 5 ]. While these data suggest that ABG can be considered a predictor of AMI prognosis, the predictive effectiveness of ABG depends on its definition and the threshold used to characterize stress hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…While increases in the use of reperfusion therapy, percutaneous coronary intervention (PCI), and secondary prevention therapy have decreased the mortality of ST-segment elevation myocardial infarction (STEMI), the incidence of in-hospital mortality remains high at 4–12% [ 1 , 2 ]. Stress hyperglycemia—defined as a transient increase in blood glucose related to the stress of illness, is a strong predictive factor for adverse outcomes in patients with acute myocardial infarction (AMI) [ 3 , 4 ], including those with non-obstructive coronary arteries (MINOCA) [ 5 ]. To explain this phenomenon, researchers have speculated that stress hyperglycemia caused by sympathetic system activation, leads to oxidative stress and endothelial dysfunctions [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In an Italian registry with around 2500 patients, it was shown that hyperglycemic patients with obstructive acute MI had higher inflammatory markers and larger infarct sizes compared to normoglycemic ones [ 21 ]. In addition, admission stress-hyperglycemia predicted higher in-hospital and long-term (3 year) mortality, regardless of diabetes, in both patients with obstructive or non-obstructive coronary arteries [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, recent guidelines and expert consensus have been characterized by further emphasizing the assessment risk factors combined with obvious cardiovascular pathological lesions in patients with diabetes [ 6 , 17 ]. The potential mechanism of diabetes as a risk factor of cardiovascular diseases might because of hyperglycemia influences the pathology of coronary microvascular, inflammation and sympathetic nervous system activity, vasospastic and structural remodeling of circulation, resulting in an increased cardiovascular risk [ 17 , 30 ]. Although our study did not provide the detailed mechanism exploration, the present study might support the notion that diabetes could impose a bad impact on the adverse outcome in patients with CAD, even in those with intermediate coronary stenosis.…”
Section: Discussionmentioning
confidence: 99%